2021
DOI: 10.1117/1.nph.8.1.015009
|View full text |Cite
|
Sign up to set email alerts
|

Improving laser standards for three-photon microscopy

Abstract: . Significance: Three-photon excitation microscopy has double-to-triple the penetration depth in biological tissue over two-photon imaging and thus has the potential to revolutionize the visualization of biological processes in vivo . However, unlike the plug-and-play operation and performance of lasers used in two-photon imaging, three-photon microscopy presents new technological challenges that require a closer look at the fidelity of laser pulses. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…initially broadening the pulses with the opposite sign of dispersion) such that the pulses subsequently compress as they propagate through the system to become transform-limited exactly at the focus point. It has been shown that for 3PE microscopy (typically requiring shorter excitation pulses but allows fordeeper imaging depths), even third-order-dispersion (TOD) is of concern [82], requiring pre-compensation using a pair of grism stretcher-compressors [83].…”
Section: Laser Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…initially broadening the pulses with the opposite sign of dispersion) such that the pulses subsequently compress as they propagate through the system to become transform-limited exactly at the focus point. It has been shown that for 3PE microscopy (typically requiring shorter excitation pulses but allows fordeeper imaging depths), even third-order-dispersion (TOD) is of concern [82], requiring pre-compensation using a pair of grism stretcher-compressors [83].…”
Section: Laser Sourcementioning
confidence: 99%
“…These lasers use low repetition rates (1 to 10 MHz) to increase the peak intensity and reduce the amount of heat delivered to the sample. Laser performance parameters including pulse shape, pulse energy, and pulse-to-pulse intensity variability used in 3PE microscopy should be occasionally measured to ensure optimal performance [82].…”
Section: Opto-mechanical Componentsmentioning
confidence: 99%
“…which is known to cause pulse broadening 7 . This is evidently shown in Figure 2(d,e) revealing that the laser pulses cannot be efficiently compressed to their theoretical limits due to the phase distortions.…”
Section: Characterisation Of the Laser Pulsementioning
confidence: 99%
“…25 Pulse characterization with FROG allows for the recovery of spectral intensity and phase using iterative spectrogram inversion algorithms and provides a ground-truth pulse width measurement. 26,27 We optimized the prism pulse compressor at 1300 nm to achieve 51 fs pulses and a pulse duration of 51 to 75 fs for 1225 to 1360 nm, except for 1250 nm, which was 104 fs [Fig. 1(b)].…”
Section: Frequency-resolved Optical Gating Pulse Measurementsmentioning
confidence: 99%